Plasminflammation—An Emerging Pathway to Bradykinin Production - Maas, Coen (Frontiers in Immunology, 2019)
Plasminogen activation is essential for fibrinolysis – the breakdown of fibrin polymers in blood clots. Besides this important function, plasminogen activation participates in a wide variety of inflammatory conditions. One of these conditions is hereditary angioedema (HAE), a rare disease with characteristic attacks of aggressive tissue swelling due to unregulated production and activity of the inflammatory mediator bradykinin. Plasmin was already implicated in this disease decades ago, but a series of recent discoveries have made it clear that plasmin actively contributes to this pathology. Collective evidence points towards an axis in which the plasminogen activation system and the contact system (which produces bradykinin) are mechanistically coupled. This is amongst others supported by findings in subtypes of HAE that are caused by gain-of-function mutations in the genes that respectively encode Factor XII or plasminogen, as well as clinical experience with the antifibrinolytic agents in HAE. This helps us to explain the inflammatory side effects of fibrinolytic therapy, presenting as angioedema or tissue edema. Furthermore, these observations motivate the development and characterization of therapeutic agents that disconnect plasminogen activation from bradykinin production.